Effect of Lactobacillus rhamnosus LGG® and Bifidobacterium animalis ssp. lactis BB-12® on health-related quality of life in college students affected by upper respiratory infections - Smith, Tracey J.; Rigassio-Radler, Diane; Denmark, Robert; Haley, Timothy; Touger-Decker, Riva (British journal of nutrition, 2013)
College students are susceptible to upper respiratory infections (URI) due to inadequate sleep, stress and close living quarters. Certain probiotic strains modulate immune function and may improve health-related quality of life (HRQL) during URI. The present study recruited apparently healthy college students and assessed the effect of probiotics on HRQL outcomes (i.e. self-reported duration, symptom severity and functional impairment of URI) in those who developed URI. Missed school and work days due to URI were also considered. Subjects (n 231) were apparently healthy college students living on campus in residence halls at the Framingham State University (Framingham, MA, USA), and were randomised to receive placebo (n 117) or probiotic-containing powder (daily dose of minimum 1 billion colony-forming units of each Lactobacillus rhamnosus LGG® (LGG®) and Bifidobacterium animalis ssp. lactis BB-12® (BB-12®); n 114) for 12 weeks. Subjects completed The Wisconsin Upper Respiratory Symptom Survey-21 to assess HRQL during URI. The final analyses included 198 subjects (placebo, n 97 and probiotics, n 101). The median duration of URI was significantly shorter by 2 d and median severity score was significantly lower by 34 % with probiotics v. placebo (P< 0·001), indicating a higher HRQL during URI. Number of missed work days was not different between groups (P= 0·429); however, the probiotics group missed significantly fewer school days (mean difference = 0·2 d) compared to the placebo group (P= 0·002). LGG® and BB-12® may be beneficial among college students with URI for mitigating decrements in HRQL. More research is warranted regarding mechanisms of action associated with these findings and the cost–benefit of prophylactic supplementation.